The trajectory of the materials originally destined to the Glossary of 'Orígenes del español' - Echenique Elizondo, María Teresa; Ribes Lorenzo, Juan Manuel (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Ramón Menéndez Pidal originally planned Orígenes del español with a glossary that was intended to be a second part of it, the Glosario del español primitivo. This task was given to the young Rafael Lapesa, but the material and data collected suffered some vicissitudes before and after the Spanish Civil War. After the death of Lapesa, Manuel Seco assumed and conducted the preparations in order to publish the materials that were given and donated long ago to the RAE - donation pursued to help the preparation and creation of the Diccionario histórico in the late 70s. From this given documentation was published a book known as Léxico hispánico primitivo. In the present study we analyse and contrast the different periods of elaboration suffered by those materials. Moreover, we note that the work initially planned as a glossary of old Castilian evolved to a Glosario iberorrománico, with a fully Hispanic amplitude, all of it still partially unpublished.
Keywords: Orígenes del español; Primitive Castilian Lexicon; erromanic glossary of the primitive Spanish